RP-182 alleviated obstruction-induced renal fibrosis by reprogramming CD206+ macrophages - Cao, Hualin; Chen, Xiaoye; Jin, Ruyue; Yang, Yunjie; Tao, Yuandong; Li, Pin; Wu, Yangyang; Chen, Guilong; Zhao, Jiawen; Wen, Jianhua; Zhao, Yutong; Wei, Liwei; et al. (Frontiers in Pharmacology, 2026)
IntroductionObstructive nephropathy is a major cause of chronic kidney disease (CKD), characterized by progressive renal fibrosis with limited treatment options. CD206+ macrophages have emerged as key drivers of fibrogenesis, yet targeted strategies against this subset remain undeveloped.MethodsUsing human ureteropelvic junction obstruction (UPJO) tissues and a murine unilateral ureteral obstruction (UUO) model, we assessed the accumulation of CD206+ macrophages and the progression of fibrosis. The therapeutic peptide RP-182, which selectively targets CD206, was administered daily to UUO mice. Histological, molecular, and flow cytometric analyses were performed to evaluate renal injury, fibrosis, inflammation, and macrophage polarization. In vitro studies using bone marrow-derived macrophages elucidated the mechanisms underlying the action of RP-182.ResultsCD206+ macrophages were significantly enriched in human UPJO kidneys and UUO mice, correlating with fibrosis severity. RP-182 treatment attenuated collagen deposition, α- SMA expression, tubular damage, and inflammatory cell infiltration in UUO kidneys. In vitro, RP-182 selectively inhibited IL-4/IL-13-induced M2 polarization and suppressed TGF- β-triggered macrophage-to-myofibroblast transition (MMT) in M2 macrophages, while sparing M1 responses. Mechanistically, RP-182 downregulated β-catenin signaling, a pathway crucial for M2 programming and MMT.DiscussionOur findings demonstrate that RP-182 alleviates obstructive renal fibrosis by specifically targeting CD206+ macrophages, inhibiting their M2 polarization and MMT via β-catenin suppression. This work highlights RP-182 as a novel macrophage- directed therapeutic candidate for progressive kidney fibrosis.